Exploring the pattern of sexual harassment in Lagos State Higher Institutions: a structural model - Airat Sulaiman, (Penerbit UKM, 2015)
This study examined the pattern of sexual harassment in higher institutions in Lagos state. Hypothesising, unlike researchers that there shall be a direct relationship between all identifi ed categories of sexual harassment behaviours thus: physical, verbal, non-verbal and quid pro quo and sexual harassment; and the report of sexual harassment is predicted by gender, physical sexual behaviour and quid pro quo. Six hundred students randomly selected from six higher institutions in Lagos State, responded to Pattern of Sexual Harassment Questionnaire (PSHQ). Results were analysed by the use of path analysis. The produced model adequately fi t the hypothesised model; the chi-square result χ2(6) = 13.02, p = 0.043 < 0.05, Root Mean Square Error of Approximation (RMSEA) 0.044 < 0.06, the Goodness of Fit Index (GFI) 0.99, Adjusted GFI (AGFI) 0.97, Normed fi t index (NFI) 0.99, Comparative fi t index (CFI) 0.98 and Incremental fi t index (IFI) 0.100 all > 0.9 all indicate suffi cient good fi tness of the model. Based on the fi ndings of the study counsellors are challenged to become more responsive than before to counselling needs of students in order to discourage sexual harassment and encourage reporting of sexual harassment.